A near infrared fluorescence imprinted sensor based on zinc oxide nanorods for rapid determination of ketoprofen. Issue 25 (3rd June 2021) - Chen, Shan; Zhou, Shu; Fu, Jinli; Tang, Sisi; Wu, Xiaodan; Zhao, Pengfei; Zhang, Zhaohui
Abstract : A near infrared fluorescence imprinted sensor with high selectivity and sensitivity was developed based on zinc oxide nanorods for determination of ketoprofen in 1.0 min. Abstract : A novel near infrared fluorescence imprinted sensor based on polyethyleneimine passivated copper-doped CdS quantum dots and zinc oxide nanorods for rapid recognition of ketoprofen was successfully prepared by sol–gel imprinting technology. The results showed that the copper-doped CdS quantum dots passivated with polyethyleneimine could improve the fluorescence lifetime and stability. Zinc oxide nanorods as carriers could improve the fluorescence response speed and sensitivity of the imprinted sensor toward ketoprofen. And the fluorescence imprinted sensor could rapidly recognize ketoprofen in just 1.0 minute. Under optimum conditions, the fluorescence intensity of the fluorescence imprinted sensor was quenched linearly by ketoprofen in the concentration range of 0.05–35.5 μM with a detection limit of 1.36 nM. The fluorescence response mechanism of the fluorescence imprinted sensor toward ketoprofen was discussed in detail, and the fluorescence quenching of the fluorescence imprinted sensor by ketoprofen was attributed to the electron transfer. The fluorescence imprinted sensor was applied to recognize ketoprofen in tap water, lake water, waste water and human urine samples rapidly with the recoveries of 97.3–103.7%. The near infrared fluorescence imprinted sensor provided a new reliable method for rapid and sensitive recognition of drugs in complex samples selectively.